2009
DOI: 10.1136/tc.2009.030981
|View full text |Cite
|
Sign up to set email alerts
|

Smoking among rural and urban young women in China

Abstract: MethodsA survey of 11 095 urban and rural women attending high school or college, aged 14–24 years, in 6 Chinese provinces was conducted. Ever-smoking (ES), current smoking, established smoking and intention to smoke frequencies were calculated. Bivariate analyses were conducted to identify possible correlates of smoking, and those found to be significant at the p=0.1 level were included in a multivariate logistical regression model to obtain adjusted OR for correlates of ES.ResultsES prevalence was 20.1%, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 13 publications
1
59
0
1
Order By: Relevance
“…Studies in China, India, Indonesia and the Dominican Republic have found that while people (including health professionals) were generally aware that smoking is harmful they were less aware of specific health risks beyond cancer, particularly for those smoking at relatively low levels 90 92–95. One study in China found that over two-thirds of female smokers thought that ‘light’ or low tar cigarettes were less harmful than regular cigarettes,96 while another Chinese study found that awareness of ‘cigarettes made for women’ (women's brands) and believing that they were less harmful to health predicted smoking experimentation in female students 97. With regards to smoking during pregnancy, a study in Pakistan found that only 7% of women knew that smoking could lead to low birth weight; only one third of women knew that smoking caused lung disease 98.…”
Section: The Impact Of Tobacco Control Policies On Women and Girlsmentioning
confidence: 99%
“…Studies in China, India, Indonesia and the Dominican Republic have found that while people (including health professionals) were generally aware that smoking is harmful they were less aware of specific health risks beyond cancer, particularly for those smoking at relatively low levels 90 92–95. One study in China found that over two-thirds of female smokers thought that ‘light’ or low tar cigarettes were less harmful than regular cigarettes,96 while another Chinese study found that awareness of ‘cigarettes made for women’ (women's brands) and believing that they were less harmful to health predicted smoking experimentation in female students 97. With regards to smoking during pregnancy, a study in Pakistan found that only 7% of women knew that smoking could lead to low birth weight; only one third of women knew that smoking caused lung disease 98.…”
Section: The Impact Of Tobacco Control Policies On Women and Girlsmentioning
confidence: 99%
“…Between 1993 and 2008, the age for smoking initiation among Chinese women has decreased significantly, and the percentage of heavy smokers (≥20 cigarettes/day) has increased dramatically [2]. A recent survey reported an alarmingly high ever smoking prevalence of 20 % among Chinese adolescent girls and young women aged 14–24 years [20]. With a huge population and a historically low smoking rate among women, China is an almost limitless potential market for the tobacco industry [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al, 2008 ), with an estimated million tobacco-related deaths annually -more than any other country -a total , which is expected to increase for decades ( Peto, Chen, & Boreham, 2009 ). There are an estimated 300 -350 million Chinese smokers, approximately 57 % -70% of men and 2 % -4% of women, constituting one-third of the world ' s smokers ( Ho et al, 2010 ;Ma et al, 2008 ;World Health Organization, 2008 ;G. Yang et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%